Silang mga kapamilya n'yo ... a descriptive study on the portrayal of single-parent and two-parent families on television - de Los Santos, Joanne S. 1977-; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This study aims to describe the portrayal of families in local family-oriented television programs and identity patterns in roles, values, and practices in single-parent and two-parent families. Specifically, it attempts to determine who the members of the Filipino family and household are and identify family values portrayed in the programs. Likewise, it aims to describe patterns observed in single and two-parent families in the aspects of roles of family members, child-rearing, decision-making, and conflicts and conflict resolution in family. To carry out the objectives, four episodes in each of the programs (Ang Munting Paraiso, Kaya ni Mister, Kaya ni Misis, Home along da Riles, and Oki Doki Doc) were recorded and analyzed from January 1-February 3, 2000. Purposeful sampling was used in picking out these family-oriented programs. A content analysis form served as instrument in facilitating the analysis of the programs. Results of the study show that family composition and values present in the programs are very much reflective of existing views and concepts on the Filipino family. The Filipino family is large in size due to its extended nature and close ties maintained by family members. Top values, observed in the programs were those of pagbabahala, pagmamahalan, and pagdadamayan. The findings also reveal that dependency and child-rearing patterns in single-parent as well as two-parent families are, in most ways, the same. In both families, children were not readily subjected to contributing to the family's finances but factors such as age and status of the child were also considered. Likewise, the top child-rearing practices of parents in single-parent and two-parent families were quite the same; they differed only in the order of the most frequent practices. However, the study found differences in patterns in the aread of decision-making and conflicts and conflict resolution. Children and others, usually relatives were more involved in the decision-making in single parent-families that in two-parent families. Also, conflicts in single-parent families occurred more often with non-family members and most of the times remained unresolved as opposed to that of two=parent families. For more generalized statements on the portrayal of aspects of family life in single and two-parent families, the study recommends a longer study period, inclusion of programs from other broadcasting channels, and consideration of viewers' views on Filipino family life. Time change, families change. Hopefully, though, media practitioners will advocate for providing more wholesome family entertainment and not serve as instruments in the deterioration of the principles and values that most families try so much to uphold.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Families -- Social conditions -- Philippines; Family Strucuture -- Philippines; Relationships, Family -- Philippines; Mass media and families -- Philippines